The effect of e-mental health interventions on academic performance in university and college students: A meta-analysis of randomized controlled trials - F. Bolinski; N. Boumparis; A. Kleiboer; P. Cuijpers; D.D. Ebert; H. Riper (Internet Interventions, 2020)
Background: Mental health symptoms are common among college and university students and these can affect their academic performance. E-mental health interventions have proven effective in addressing mental health complaints but their effect on academic performance has not been synthesized yet. Objectives: To synthesize the evidence from randomized controlled trials for the effectiveness of e-mental health interventions on academic performance in college and university students compared to inactive controls. Data sources and eligibility criteria: We searched six databases (PubMed, Cochrane library, CINAHL, ERIC, PsycINFO, Web of Science) during the period January 2000 until September 2019 for randomized controlled trials that reported on e-mental health interventions (guided or unguided) for college and university students and measured academic performance (e.g. grade point average). Study appraisal and synthesis methods: Study and participant characteristics and the academic performance measures at post-intervention were extracted. The latter were pooled and Hedges' g was calculated as the effect size. Heterogeneity and publication bias were investigated. Results: Six studies containing 2428 participants were included in the meta-analysis. These focussed on either mood and anxiety or alcohol and tobacco use. The pooling of data resulted in a small but non-significant effect of g = 0.26 (95% CI, −0.00, 0.52; p = .05) on academic performance, favouring e-mental health interventions over inactive controls. Interventions had positive effects on depression (g = −0.24) and anxiety (g = −0.2). Heterogeneity was high. Discussion: Despite the small and non-significant effect, our meta-analysis points to a promising direction for the effectiveness of e-mental health interventions on academic performance. Yet, these results must be interpreted with caution, as heterogeneity was high and few studies on the effectiveness of e-mental health interventions for students reported academic performance measures.